2010
DOI: 10.1111/j.1438-8677.2009.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Poplar volatiles – biosynthesis, regulation and (eco)physiology of isoprene and stress‐induced isoprenoids

Abstract: Plants interact with their environment through a wide variety of biogenic volatile organic compounds (BVOCs), with isoprenoids ( identical with terpenes), i.e. isoprene, mono- and sesquiterpenes, playing an important role. Isoprene, a hemiterpene, is the simplest isoprenoid compound mainly emitted by tree species like poplars, oaks and willows. Woody plants alone comprise 75% of the global isoprene emitted to the atmosphere. Due to its significant influence on atmospheric chemistry, research has been focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 136 publications
1
45
0
1
Order By: Relevance
“…It is generally recognized that monoterpenes in BVOC non-storing plants are produced in the methylerythritol-phosphate (MEP) pathway located in chloroplasts, where photosynthetic processes provide the major bulk of primary carbon substrate and co-factors for the biosynthesis of isoprenoid precursors thus shaping the light responses of emissions (Loreto et al, 1996;Niinemets et al, 2002;Rasulov et al, 2009). Light activation of some enzymes in the MEP pathway might further contribute to positive light effects on emissions especially in the longer term control (Rasulov et al, 2009;Rivasseau et al, 2009;Schnitzler et al, 2010). Light dependency is more uncertain for SQT emissions, whose biosynthesis are thought to proceed in the cytosol.…”
Section: Light and Temperature Responses And Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally recognized that monoterpenes in BVOC non-storing plants are produced in the methylerythritol-phosphate (MEP) pathway located in chloroplasts, where photosynthetic processes provide the major bulk of primary carbon substrate and co-factors for the biosynthesis of isoprenoid precursors thus shaping the light responses of emissions (Loreto et al, 1996;Niinemets et al, 2002;Rasulov et al, 2009). Light activation of some enzymes in the MEP pathway might further contribute to positive light effects on emissions especially in the longer term control (Rasulov et al, 2009;Rivasseau et al, 2009;Schnitzler et al, 2010). Light dependency is more uncertain for SQT emissions, whose biosynthesis are thought to proceed in the cytosol.…”
Section: Light and Temperature Responses And Interactionsmentioning
confidence: 99%
“…Since then, light and temperature responses of BVOC emissions have been measured on at least 60 different plant species and many other studies have been conducted to gain more insight into the controls over emissions (see reviews by Loreto and Schnitzler, 2010;Monson et al, 2007;Schnitzler et al, 2010;Sharkey et al, 2008). Despite this, our understanding of the variability and correctness of these responses is still insufficient especially for BVOCs other than isoprene .…”
Section: Introductionmentioning
confidence: 99%
“…Poplar leaves invest a significant amount of recently fixed carbon in isoprene biosynthesis (Delwiche and Sharkey, 1993;Schnitzler et al, 2010;Ghirardo et al, 2011) to cope with abiotic stresses (Sharkey, 1995;Velikova and Loreto, 2005;Behnke et al, 2007Behnke et al, , 2010bBehnke et al, , 2013Vickers et al, 2009;Loreto and Schnitzler, 2010;Sun et al, 2013b), although there are indications that other protective mechanisms can partially compensate the lack of isoprene emission in genetically transformed poplars Way et al, 2013). It has been suggested that in isoprene-emitting (IE) species, most of the carbon that passes through the MEP pathway is used for isoprene biosynthesis (Sharkey and Yeh, 2001).…”
mentioning
confidence: 99%
“…MeSA is emitted by many different plant species, in response to various types of stress, not only the ones considered here (e.g. Vuorinen et al, 2007;Blande et al, 2010;Schnitzler et al, 2010). Assuming Case 2 SIE, model calculated MeSA concentrations in the gas-phase are relatively high; depending on the assumptions regarding MeSA-deposition and NO 3 -reactivity, the average MeSA concentrations for the period Mar-Oct at Hyytiälä are from 110 to 260 ppt(v); see trations are of the same order of magnitude as observed by Karl et al (2008).…”
Section: Importance Of Stress-induced Mesa Emissionssensitivity Testsmentioning
confidence: 99%